Introduction of the Surgical Site Fire Risk Assessment at The Lister Hospital, part of HCA Healthcare UK. Issue 5 (May 2019) - Parremore, Rose
Introduction: A surgical site fire within the operating theatres is a continuous risk in modern surgery. When such an event does happen, clinical personnel can feel stunned, because such events are rare, and often happen rapidly. At The Lister Hospital, part of HCA Healthcare UK, a Fire Risk Assessment Tool and Protocol was developed to reduce such risks. Method: Reviewing the scholarly literature and case studies relating to surgical site fires provides information and recommendations to highlight and improve such dangerous incidents from occurring in the future. Conclusion: From the review of literature, two extensively documented cases of surgical site fire concluded in the identification of the elements of the fire triangle that create risk. From the recommendations a Fire Risk Assessment Tool and Protocol were developed and implemented at The Lister Hospital, including an addition to the WHO five Steps to Safer Surgery Checklist.